Greenhouse technology and management Nicolas Castilla ; translated by Esteban J. Baeza ; reviewed by A.P. Papadopoulos. - Castilla, Nicolas (CABI, 2013)
"Greenhouse cultivation has expanded in recent decades with increased demand for horticultural production. This book covers current technologies and management practices of general greenhouse production, with a particular emphasis on plastic greenhouses and vegetable growing. The author begins by addressing the natural greenhouse microclimate, in the context of managing greenhouse systems such as ventilation, cooling, heating, carbon dioxide enrichment, light management, crop physiology, greenhouse design and construction criteria. The book then moves on to cover other issues of greenhouse management including irrigation and fertilization, soil and substrate cultivation, plant protection, regulation, economic analysis, environmental impact, and post-harvest, production strategies and marketing. Providing an integrated approach to greenhouse production this practical text aims to provide clear advice on optimising the yield and quality of crops grown under greenhouse conditions."--Publisher's website